Islamic Value-Based Transformational Leadership, Digital Transformation, and Quality Culture in Pesantren-Based Madrasah Aliyah - Jailani Syahputra Siregar; Betti Megawati; Nursalimah Nursalimah; Ruwaidah Ruwaidah (Journal of General Education and Humanities, 2026)
Digital transformation has reshaped educational governance and requires Islamic educational institutions to adapt not only through technological innovation but also through leadership, organizational culture, and quality improvement. In Islamic boarding school-based Madrasah Aliyah, this transformation is more complex because it must preserve Islamic values and institutional identity while responding to rapid technological change. This study aims to synthesize the literature on how Islamic values-based transformational leadership supports digital transformation and quality culture in Islamic educational management. This study employed a Systematic Literature Review (SLR) following the PRISMA 2020 guidelines. Literature published between 2021 and 2026 was retrieved from Scopus, Web of Science, ERIC, ScienceDirect, and Google Scholar. A total of [N] records were identified, [N] duplicates were removed, [N] articles were screened, [N] were excluded after eligibility assessment, and 10 core studies (2023–2026) were included in the final thematic synthesis. The findings reveal four recurring themes: (1) Islamic values as a source of leadership legitimacy, (2) transformational leadership as the driver of digital transformation, (3) quality culture as the outcome of institutionalized organizational practices, and (4) structural and cultural barriers to change. This review proposes a conceptual model in which Islamic values strengthen transformational leadership, which, in turn, supports digital transformation and the institutionalization of a quality culture. The study contributes theoretically by integrating these four dimensions into a coherent framework and provides practical implications for school leaders, Islamic boarding school administrators, and policymakers seeking to strengthen digital transformation while maintaining the distinctive values of Islamic education.